2021
DOI: 10.3389/fvets.2020.586033
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying Protective Role of Quercetin on Copper Sulfate-Induced Nephrotoxicity in Mice

Abstract: Copper overload is an established cause of nephrotoxicity, but the precise molecular mechanism remains unknown. Our study aimed to investigate the molecular mechanism of copper sulfate (CuSO4)-induced nephrotoxicity and the protective effect of the natural compound quercetin using a mouse model. Mice were orally administered CuSO4 only (200 mg/kg per day), or co-administered CuSO4 (200 mg/kg per day) plus quercetin (25, 50, or 100 mg/kg per day), or quercetin only (100 mg/kg per day), or vehicle for 28 days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…The cross-talk between these pathways has indeed been previously reported, where upregulation of renal Nrf2/ HO-1 was concomitantly encountered together with a decrease in renal TNF-α by ergothioneine in cisplatininduced nephrotoxicity, 34 by phenethyl isothiocyanate in streptozotocin-induced diabetic nephropathy, 35 and by quercetin on copper sulfate-induced nephrotoxicity. 36 Similar findings have been reported linking the upregulation of renal Nrf2/HO-1 to caspase 3 downregulation by ergothioneine in cisplatin-induced nephrotoxicity, 34 by camel milk in cyclosporine-induced nephrotoxicity, 37 and by thymoquinone in diclofenacinduced acute kidney injury. 38 However, despite all previous reports, it is extremely difficult to hypothesize a cause-effect relationship between these complex pathways.…”
Section: Discussionsupporting
confidence: 71%
“…The cross-talk between these pathways has indeed been previously reported, where upregulation of renal Nrf2/ HO-1 was concomitantly encountered together with a decrease in renal TNF-α by ergothioneine in cisplatininduced nephrotoxicity, 34 by phenethyl isothiocyanate in streptozotocin-induced diabetic nephropathy, 35 and by quercetin on copper sulfate-induced nephrotoxicity. 36 Similar findings have been reported linking the upregulation of renal Nrf2/HO-1 to caspase 3 downregulation by ergothioneine in cisplatin-induced nephrotoxicity, 34 by camel milk in cyclosporine-induced nephrotoxicity, 37 and by thymoquinone in diclofenacinduced acute kidney injury. 38 However, despite all previous reports, it is extremely difficult to hypothesize a cause-effect relationship between these complex pathways.…”
Section: Discussionsupporting
confidence: 71%
“…Shen et al (12) indicated that quercetin was able to decrease the secretion of IL-6, TNF-α and IL-1β in the serum and ankle joint tissues. In addition, another previous study suggested that quercetin attenuated copper sulfate-induced upregulation of TNF-α, IL-6 and IL-1β (13). The aforementioned results are consistent with those observed in the present study, indicating that quercetin has an anti-inflammatory effect.…”
Section: Discussionsupporting
confidence: 93%
“…The strong antioxidant effect of QUR was attributed to its hydroxyl group on the side phenyl ring, which gives it the ability to scavenge free radical, and improve enzymatic antioxidants and glutathione. The molecular mechanisms may include regulation of signaling pathways such as Nrf2/HO-1, MAPK, and TLR4/PI3K [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…QUR was reported to have an immunoregulatory activity in human dendritic cells, where it shifted the immune balance from inflammation to resolution [ 66 ]. The protective anti-inflammatory activity of QUR was previously described in a mouse nephrotoxicity model [ 50 ] and in rats and mice with chronic prostatitis and rheumatoid arthritis [ 67 , 68 ]. This activity of QUR was supposed to be mediated via suppression of the activation of NLRP3 inflammasome and regulating SIRT1 pathway [ 69 ], and downregulation of NF-κB [ 50 ], inq21f, and MAPK signaling pathways [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation